Educational Methodical and Technological Knowledge in Library and Information Activities - I. S. Pilko (Библиосфера, 2025)
Digital and sociocultural transformations have influenced changes in the content of library activities and the expansion of its boundaries. The emergence of new methods and forms of working with information and library users, the development of new communication channels have updated the issue of the competencies of a modern librarian in a wide range of information and communication, cultural, educational, educational, scientific-analytical, social-pedagogical, marketing and other technologies. The need to track and understand the tools that are relevant for library practice is an important task of library and bibliographic sciences; timely integration of new methods and technologies into the process of training library personnel is a task of professional education. The purpose of the article is to assess the cognitive and didactic potential of a qualified methodical and technological description of library and information activities for developing the competence of library staff and improving the quality of traditional and innovative products and services provided by libraries. Based on the analysis of scientific and educational publications for higher library schools, terminological standards, the “blurriness” and ambiguity of the definitions of the concepts “methodic” and “technology” in relation to library and information activities have been established, as well as the lack of clear ideas about the structure and content of technological and methodical description of library processes in educational publications. In particular, the limitation of technological description solely to the process algorithm has become widespread; the description of methods in demand in library practice is characterized by a high degree of subjectivity. As a result of the analysis, specific features of methodical and technological knowledge are formulated in relation to the social and humanitarian sphere, which may be in demand to substantiate the principles of delimiting one from the other. A framework structure for the technological description of library processes, that is acceptable for educational publications in the library and information sector, has been identified. The issue of their methodical description deserves special and careful consideration.